Aspirin Use Is Associated with a Reduced Incidence of Hepatocellular Carcinoma: A Systematic Review and Meta‐analysis. Issue 1 (13th November 2020) - Memel, Zoe N.; Arvind, Ashwini; Moninuola, Oluwatoba; Philpotts, Lisa; Chung, Raymond T.; Corey, Kathleen E.; Simon, Tracey G.
Abstract : Hepatocellular carcinoma (HCC) is the third‐leading cause of cancer‐related death worldwide, with a growing incidence and poor prognosis. While some recent studies suggest an inverse association between aspirin use and reduced HCC incidence, other data are conflicting. To date, the precise magnitude of risk reduction—and whether there are dose‐dependent and duration‐dependent associations—remains unclear. To provide an updated and comprehensive assessment of the association between aspirin use and incident HCC risk, we conducted a systematic review and meta‐analysis of all observational studies published through September 2020. Using random‐effects meta‐analysis, we calculated the pooled relative risks (RRs) and 95% confidence intervals (CIs) for the association between aspirin use and incident HCC risk. Where data were available, we evaluated HCC risk according to the defined daily dose of aspirin use. Among 2, 389, 019 participants, and 20, 479 cases of incident HCC, aspirin use was associated with significantly lower HCC risk (adjusted RR, 0.61; 95% CI, 0.51‐0.73; P ≤ 0.001; I 2  = 90.4%). In subgroup analyses, the magnitude of benefit associated with aspirin was significantly stronger in studies that adjusted for concurrent statin and/or metformin use (RR, 0.45; 95% CI, 0.28‐0.64) versus those that did not ( P heterogeneity  = 0.02), studies that accounted for cirrhosis (RR, 0.49; 95% CI, 0.45‐0.52) versus those that did not ( P heterogeneity  = 0.02), and studies that confirmed HCC through imaging/biopsy (RR, 0.30; 95% CI, 0.15‐0.58) compared with billing codes ( P heterogeneity  < 0.001). In four studies, each defined daily dose was associated with significantly lower HCC risk (RR, 0.98; 95% CI, 0.97‐0.98), corresponding to an 8.4% risk reduction per year of aspirin use. Conclusion: In this comprehensive systematic review and meta‐analysis, aspirin use was associated with a significant reduction in HCC risk. These benefits appeared to increase with increasing dose and duration of aspirin use.